Effect of Topical Noni (Morinda citrifolia L.) Leaf Extract Paste in Carrageenan-induced Paw Edema on Wistar Rats - Indah Puti Rahmayani Sabirin; Euis Reni Yuslianti (Universitas Islam Bandung, 2019)
The inflammatory response is one of natural process in the body to protect itself following tissue injury, but it can cause discomfort. Noni (Morinda citrifolia L.) leaf known as a traditional medicament to help reduce the inflammatory effect. The leaves empirically applied as a wrapping on fever or wound. The purpose of this study was to identify the anti-inflammatory effect of topical noni leaf extract paste in 5% and 10% concentration by examination of Wistar rat paw edema induced by λ-carrageenan. Twenty-four Wistar rats divided into four groups, which were negative control, positive control with diclofenac sodium 1% gel, 5% noni leaf, and 10% noni leaf paste groups. Paw edema was induced by intraplantar injection of 1% λ-carrageenan to every rat. Every treatment subsequently applied in the plantar area before injection, and the changed paw volume measured with plethysmometer at minutes 0, 30, 60, and 90. This study was at the Animal Laboratory, Faculty of Medicine, Universitas Jenderal Achmad Yani, Cimahi city in October–December 2017. The result displayed that the minimum volume after 90 minutes was on 5% and 10% noni leaf paste group, which is 1.00 mL. Kruskal-Wallis test result of inflammatory percentage was significantly different among every group in each examination time (p<0.05). Post-hoc test showed that inflammatory reduction on paw edema with noni leaf paste application on both concentrations were significantly different compared to the negative control. However, it was not different from the positive control group. This study showed that application of noni leaf paste in 5% and 10% concentration could help reduce inflammatory response on skin possibly by the active anti-inflammatory ingredients of noni leaf. EFEK PASTA EKSTRAK DAUN MENGKUDU (MORINDA CITRIFOLIA L.) TOPIKAL TERHADAP EDEMA KAKI TIKUS GALUR WISTAR YANG DIINDUKSI KARAGENANInflamasi adalah proses alami tubuh untuk melindunginya setelah cedera, namun hal tersebut dapat menyebabkan ketidaknyamanan. Daun mengkudu (Morinda citrifolia L.) dikenal sebagai obat tradisional untuk menurunkan efek inflamasi yang secara empiris digunakan untuk mengobati demam dan luka. Tujuan penelitian ini adalah mengetahui efek anti-inflamasi pasta ekstrak daun mengkudu melalui pemeriksaan edema kaki tikus yang diinduksi karagenan-λ. Dua puluh empat tikus galur Wistar dibagi menjadi 4 kelompok, yaitu kontrol negatif dengan akuades, kontrol positif (aplikasi gel Na diklofenak 1%), serta perlakuan pasta daun mengkudu 5% dan 10%. Edema dibuat dengan menginjeksi intraplantar tikus dengan 1% karagenan-λ pada tiap kelompok. Tiap-tiap perlakuan diaplikasikan sebelum tikus diinjeksi dan perubahan volume kaki tikus diukur dengan pletismometer di menit ke-0, 30, 60, dan 90. Penelitian ini dilakukan di Laboratorium Hewan, Fakultas Kedokteran, Universitas Jenderal Achmad Yani, Kota Cimahi pada Oktober–Desember 2017. Hasil pengukuran memperlihatkan penurunan volume edema kaki terkecil setelah 90 menit pada kelompok pasta daun mengkudu 10%, yaitu 1,00 mL. Hasil Uji Kruskal-Wallis terhadap persentase inflamasi berbeda nyata pada tiap kelompok dan tiap waktu pengamatan (p<0,05). Hasil uji beda menunjukkan bahwa penurunan inflamasi kaki tikus pada perlakuan pasta daun mengkudu kedua konsentrasi berbeda nyata dibanding dengan kontrol negatif, tetapi tidak berbeda dengan kontrol positif. Penelitian ini menunjukkan bahwa pasta daun mengkudu 5% dan 10% dapat membantu menurunkan reaksi inflamasi kulit dan efeknya sejalan dengan Na diklofenak karena zat aktif yang bersifat anti-inflamasi dalam daun mengkudu.